Impact of surface chemistry of upconversion nanoparticles on time-dependent cytotoxicity in non-cancerous epithelial cells - Susanne Märkl; Frédéric Przybilla; Reinhard Rachel; Thomas Hirsch; Max Keller; Ralph Witzgall; Yves Mély; Joachim Wegener (Scientific Reports)
Abstract The application of upconversion nanoparticles (UCNPs) for cell and tissue analysis requires a comprehensive understanding of their interactions with biological entities to prevent toxicity or harmful effects. Whereas most studies focus on cancer cells, this work addresses non-cancerous cells with their regular in vitro physiology. Since it is generally accepted that surface chemistry largely determines biocompatibility in general and uptake of nanomaterials in particular, two bilayer surface coatings with different surface shielding properties have been studied: (i) a phospholipid bilayer membrane (PLM) and (ii) an amphiphilic polymer (AP). Both surface modifications are applied to (12–33) nm core-shell UCNPs NaYF4(Yb, Er)@NaYF4, ensuring colloidal stability in biological media. The impact of UCNPs@AP and UCNPs@PLM on non-cancerous epithelial-like kidney cells in vitro was found to differ significantly. UCNPs@PLM did not exhibit any measurable effect on cell physiology, even with prolonged exposure. In contrast, UCNPs@AP caused changes in cell morphology and induced cell-death after approximately 30 h. These variations in toxicity are attributed to the distinct chemical stability of these particles, which likely influences their intracellular disintegration.